Investigation of non-uniform carbonation in strain-hardening magnesia composite (SHMC) and its impacts on fiber-matrix interface and fiber-bridging properties - Gu, Lei (2024)
Unlike Portland cement, the reactive magnesia cement (RMC) develops its strength via carbonation. Non-uniform microstructure and properties due to the varied carbonation degree across cross-section depth have thus been observed. However, the existing micromechanics design theory employs uniform material properties (cementitious matrix and fiber-matrix interface characteristics) to design strain-hardening composites. This research investigated such non-uniform carbonation in a strain-hardening magnesia composite (SHMC) and its impacts on fiber-matrix interface and fiber-bridging properties. Results showed that mineral phase composition (of the cementitious matrix) and fiber-matrix interface properties across cross-section depth are highly non-uniform in SHMC due to varied carbonation degrees. The outer layer exhibited a much higher carbonation degree with significantly stronger fiber-matrix friction, while the inner core showed negligible carbonation with distinct fiber-matrix properties. Insights gained from the micro-scale investigation were used to calculate the fiber-bridging constitutive law of SHMC with non-uniform carbonation across cross-section depth and to assess its strain-hardening performance. This investigation highlights the importance and necessity of considering non-uniform carbonation in the modeling and design of SHMC. The study presents a framework for the consideration of non-uniform micromechanical parameters in the design of strain-hardening cementitious composites.